2D Hexagonal Finite Fuzzy Cellular Automata - Rajasekar, M.; Jacob, Lekha Susan; Anbu, R. (Communications in Mathematics and Applications, 2022)
In this paper 2D hexagonal finite fuzzy cellular automata defined by fuzzy transition of local rules based on hexagonal cell structure are studied. Here the inverse problem of 2D hexagonal finite fuzzy cellular automata is also studied.
Keywords: Two dimensional hexagonal fuzzy cellular automta; Matrix algebra; Null boundary condition; Periodic boundary condition